When Faith Meets Value: How Religiosity Moderates Price Sensitivity in Muslim Restaurant Choice - Syam, Andi Hendra; Hafipah, Hafipah; Nuryadin, Andi; Nurmega, Nurmega; Pragemini, Pragemini (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study investigates how Muslim consumers form purchase intentions toward Muslim-identified restaurants in an environment where halal compliance is a given rather than a differentiator. It introduces a conceptual model that integrates product quality and price sensitivity, moderated by religiosity, to explain value-based trade-offs in faith-aligned consumption. Using a cross-sectional survey of Indonesian Muslim diners and Partial Least Squares Structural Equation Modeling, the findings reveal that quality strongly drives intention, price sensitivity acts as a deliberative filter, and religiosity weakens the deterrent effect of price concerns. Interestingly, religiosity exerts no direct influence on pricing perception, suggesting its role is interpretive rather than economizing. The study contributes to both halal marketing and identity salience theory by reconfiguring how religiosity functions in value judgment. For managers, the findings underscore that religious branding alone is insufficient—quality consistency, transparent pricing, and ethical storytelling are essential for sustaining consumer trust.